2021
DOI: 10.1002/kjm2.12442
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA XIST alleviates sepsis‐induced acute kidney injury through inhibiting inflammation and cell apoptosis via regulating miR‐155‐5p/WWC1 axis

Abstract: Sepsis is characterized by a severe inflammatory response throughout the whole body and can induce acute kidney injury (AKI). This research aimed to investigate the regulatory mechanisms underlying miR‐155‐5p in sepsis‐induced AKI. CLP‐treated mice were used as an in vivo model of sepsis‐induced AKI, and LPS‐treated HK‐2 and TCMK‐1 cells were used as in vitro models. Bioinformatics analyses and mechanistic assays were utilized to reveal the relationships between molecules. H&E staining was used to reveal morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Among the upstream lncRNAs of hsa-let-7b-5p, only XIST has been found to be involved in sepsis regulation. Studies have shown that silencing or downregulation of XIST expression protects against sepsis-induced multiorgan dysfunction (Wang et al, 2021;Wang and Cao, 2022). Findings from those studies are consistent with our prediction that XIST−hsa-let-7b-5p−TGFBR1/DUSP1 may be a vital ceRNA regulatory network in sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…Among the upstream lncRNAs of hsa-let-7b-5p, only XIST has been found to be involved in sepsis regulation. Studies have shown that silencing or downregulation of XIST expression protects against sepsis-induced multiorgan dysfunction (Wang et al, 2021;Wang and Cao, 2022). Findings from those studies are consistent with our prediction that XIST−hsa-let-7b-5p−TGFBR1/DUSP1 may be a vital ceRNA regulatory network in sepsis.…”
Section: Discussionsupporting
confidence: 91%
“…lncRNA CTBP1-AS2 targets miR-155-5p and upregulates FOXO1 to abate HG-elicited proliferation, oxidative stress, ECM accumulation, and inflammation in human glomerular mesangial cells [ 32 ]. lncRNA XIST targets miR-155-5p and upregulates WWC1 to dampen inflammatory cytokine generation and cell apoptosis, hence attenuating acute kidney injury induced by sepsis [ 33 ]. Here, we discovered that miR-155-5p’s expression was greatly uplifted in the plasma and lung tissues of the SAP-ALI rats, but SGB notably drove down its expression.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of Xist expression on inflammation appears to be context dependent and has not yet been investigated in the context of NSCs. Some studies have found that it promotes inflammation ( Chen et al., 2021 ; Yan et al., 2022a ) and others that it reduces inflammation ( Shenoda et al., 2021 ; Wang and Cao, 2022 ). Therefore the apparently contradictory patterns of expression observed in Sox2ot and Xist may be due to multiple regulatory mechanisms acting in parallel.…”
Section: Discussionmentioning
confidence: 99%